Insertion mechanics of amorphous SiC ultra-micro scale neural probes. (1st April 2022) - Geramifard, Negar; Dousti, Behnoush; Nguyen, Christopher; Abbott, Justin; Cogan, Stuart F; Varner, Victor D
Abstract: Objective . Trauma induced by the insertion of microelectrodes into cortical neural tissue is a significant problem. Further, micromotion and mechanical mismatch between microelectrode probes and neural tissue is implicated in an adverse foreign body response (FBR). Hence, intracortical ultra-microelectrode probes have been proposed as alternatives that minimize this FBR. However, significant challenges in implanting these flexible probes remain. We investigated the insertion mechanics of amorphous silicon carbide (a-SiC) probes with a view to defining probe geometries that can be inserted into cortex without buckling. Approach . We determined the critical buckling force of a-SiC probes as a function of probe geometry and then characterized the buckling behavior of these probes by measuring force–displacement responses during insertion into agarose gel and rat cortex. Main results. Insertion forces for a range of probe geometries were determined and compared with critical buckling forces to establish geometries that should avoid buckling during implantation into brain. The studies show that slower insertion speeds reduce the maximum insertion force for single-shank probes but increase cortical dimpling during insertion of multi-shank probes. Significance. Our results provide a guide for selecting probe geometries and insertion speeds that allow unaided implantation of probes into rat cortex. The design approach is applicable to other animal models where insertion of intracortical probes to a depth of 2 mm is required.